The Effects of Social Accountability in Medical Education on the Knowledge of Occupational Health Personnel working in the Cement Industry in Iran - Seyedeh Negar Assadi (Tabriz University of Medical Sciences, 2014)
Introduction: Social accountability in medical education is an essential part of the health education process. According to the current needs in health education, social accountability in medical education is useful for increasing the overall knowledge of students, helping them to reach their maximum competency. The objective of this study was to determine the effects of social accountability medical sciences education on the knowledge of occupational health personnel working in the cement field.Methods: This study was a semi-experimental study that was conducted by using the curriculum of the Ministry of Health. The occupational health course was taught as a social accountability in medical education course in order to increase knowledge in occupational health personnel of the cement industries, and then the grades of those personnel were analyzed by SPSS 11.5. Mean, standard deviation, and a t-test with P<0.05 were calculated. The test incorporated aspects of students' knowledge, attitude and practice. Results: The total grade of the occupational health workers at the pre-test (before the accompanying workshops) was 4.39±2.10, and at the post-test (after the workshops), it was 17.52±3.28 with t = -14.274 and P<0.001 had significant differences. The grades in all of the educational items were statistically significant after the workshops. Conclusion: According to the grades, the social accountability in medical education course had a positive effect on the knowledge of the occupational health personnel of cement industries.